Low-dose irradiation could mitigate osteoarthritis progression via anti-inflammatory action that modulates mitochondrial function. (May 2022) - Kim, Byoung Hyuck; Bae, Hyun Cheol; Wang, Sun Young; Jang, Bum-Sup; Chang, Ji Hyun; Chie, Eui Kyu; Yi, Hyon-Seung; Kwon, Jeanny; Han, Hyuk-Soo; Kim, Hak Jae
Highlights: Low-dose radiation therapy (LDRT) decreased the expression of pro-inflammatory factor MMP13 in chondrocytes. By contrast, COL2 protein expression was increased. LDRT induced large transcriptomic changes in both chondrocytes/synoviocytes, especially in mitochondrial activities. Gene set variation analysis demonstrated inverted U-shaped response in several categories, such as mitochondrial unfolded protein responses and extracellular matrix interactions. Growth differentiation factor 15 (GDF15), which is a mitohormetic signaling factor, was increased after LDRT and mediated the anti-inflammatory effects. OA rats treated with LDRT exhibited a decreased OA severity and reduced osteoclast activity when compared with the no-irradiation group. Abstract: Purpose: The use of low-dose radiation therapy (LDRT) for osteoarthritis (OA) are rarely implemented, except in some European regions. Its clinical effects are controversial but little is known about how LDRT affects actual disease progression. We conducted a preclinical study to reveal the potential underlying mechanisms related to its disease modifying abilities. Methods and Materials: Using primary cultured human chondrocytes and synovium-derived cells obtained from OA patients, the effects of LDRT were measured by quantitative real-time PCR, western blotting, and mRNA sequencing. For in vivo validation, a surgically-induced isolated OA model was used after anterior cruciate ligament transection or surgical destabilization of the medial meniscus. Results: LDRT decreased the expression of pro-inflammatory factor matrix metalloproteinase 13 (MMP13) in chondrocytes. By contrast, collagen type 2 (COL2) protein expression was increased. LDRT induced large transcriptomic changes in both chondrocytes/synoviocytes, especially in mitochondrial activities. Gene set variation analysis demonstrated inverted U-shaped response in several categories, such as mitochondrial unfolded protein responses and extracellular matrix interactions. Growth differentiation factor 15 (GDF15), which is a mitohormetic signaling factor, was increased after LDRT and mediated the anti-inflammatory effects. Aggrecan was increased in synoviocyte's medium and TNF-α was decreased in chondrocyte's medium after LDRT. Conversely, knockdown of GDF15 did not result in decreased MMP13 expression by LDRT. Next, OA rats treated with LDRT exhibited a decreased OA severity when compared with the no-irradiation group at 10 weeks post-surgery (mean OARSI score 3.7 in 0 Gy, 2.8 in 0.5 Gy, and 1.8 in 1 Gy; p  = 0.003). Osteoclast activity was significantly reduced in the LDRT group. Conclusions: Taken together, these data show that LDRT could mitigate osteoarthritis progression by exerting its anti-inflammatory effects via mitochondrial function modulation.